Study: Indoor air quality poses possible health threat - New Straits Times (2012)
Building occupants in the Klang Valley reported a higher prevalence of illnesses such as fatigue, headaches and coughs compared to those in problematic buildings in Scandinavia:This shows that the reported cases of illnesses in the Klang Valley are at a critical level which could be affecting the health and productivity of building occupants, says a Nippon Paint study recently.